2018
DOI: 10.12659/msm.912868
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Serum Levels Are Elevated in Individuals with Degenerative Cervical Myelopathy and Are Correlated with Symptom Severity

Abstract: BackgroundFew studies have investigated systemic inflammation levels in degenerative cervical myelopathy (DCM). This study evaluated the concentration of inflammatory cytokines in DCM patients and assessed whether they can predict symptom severity.Material/MethodsA total of 40 consecutive DCM patients and 10 healthy volunteers were included in this study. Concentrations of interleukin (IL)-1β, IL-6, interferon-γ, and tumor necrosis factor-α were compared between DCM patients and normal controls. Spearman’s cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Previous studies also have shown that IL-6 was significantly increased in intervertebral disc degeneration tissues and positively correlated with the degree of intervertebral disc degeneration and symptom severity. For example, Du et al [ 22 ] found that serum IL-6 levels were elevated during disc degeneration, and the concentration could predict the severity of symptoms. Our results also showed a statistically significant difference in serum IL-6 levels between the high-score group (total score > 18) and the low-score group (total score ≤ 18).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also have shown that IL-6 was significantly increased in intervertebral disc degeneration tissues and positively correlated with the degree of intervertebral disc degeneration and symptom severity. For example, Du et al [ 22 ] found that serum IL-6 levels were elevated during disc degeneration, and the concentration could predict the severity of symptoms. Our results also showed a statistically significant difference in serum IL-6 levels between the high-score group (total score > 18) and the low-score group (total score ≤ 18).…”
Section: Discussionmentioning
confidence: 99%
“…18,19,37,38 In a rat myelopathy model, infusion of IL-6 resulted in motor dysfunction and mechanical allodynia threshold decline. 18 Likewise, IL-6 and IL-8 were shown to be elevated in the CSF of patients with myelopathy compared with control groups, scaling with the severity of spinal cord compression. 18,19,37,38 IL-6 concentrations have also been shown to be elevated in the serum of myelopathy patients.…”
Section: Discussionmentioning
confidence: 99%
“…18,19,37,38 IL-6 concentrations have also been shown to be elevated in the serum of myelopathy patients. 18 While the understanding of human cytokine profiles of patients with isolated radiculopathy is more limited, robust animal research studies have measured inflammatory markers in the setting of nerve root injury. 35,37,39,40 Recombinant TNF-α applied directly to the rat DRG, to mimic disc herniation, resulted in apoptosis of the DRG cellular nuclei.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations